Seed-borne Fungi of Wheat Cultivars in Pakistan (Biological Sciences - PJSIR, 2022)
an average yield ofl825 kg/ha [1]. Despite the developmentof high yielding varieties and improved cultural practices,diseases still playa significant role in reducing the productivityof wheat crop.